Heat Unit Optimization as Harvest Criteria on Banana “Barangan” at Five Time Anthesis - Turi Handayani; Winarso Drajad Widodo; Ani Kurniawati; Ketty Suketi (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2020)
Harvest time can affect the shelf life and quality of fruit during storage, therefore, the right method is needed in accordance with harvest time. This study aimed to optimize heat units as a harvest criteria of Barangan banana and its effect on fruit quality. The study was conducted at Sukabumi, West Java PTPN VIII in October 2018 to February 2019 using a Randomized Complete Block Design with single factor and five anthesis time: anthesis 1 (October 13rd 2018), anthesis 2 (October 20th 2018), anthesis 3 (October 27th 2018), anthesis 4 (November 03rd 2018), anthesis 5 (November 10th 2018). The results showed Barangan banana was harvested at a minimum heat unit of 1 234.50±2.76 0C degree days with a harvest time of 72-73 days and a shelf life of 16-17 days and can be used as a harvesting criteria. Different time of anthesis did not affect to harvested fruit size, shelf life, weight loss, physical quality and chemical quality of fruit. Keywords: fruit quality, maturity, shelf life, temperature, weight loss